Outside CEOs’ Hesitancy Toward Environmental Responsibility and the Governance Role of Board Social Capital: Evidence from Pollution-Intensive Firms in China - Hailiang Zou; Simei Huang (Administrative Sciences)
While outside chief executive officers (CEOs) are often viewed as catalysts for strategic change compared to their inside counterparts, this study reveals their potential to undermine firms’ environmental responsibility. Integrating agency theory with social capital theory, we investigate whether and how board-level social capital can moderate the sustainability risks associated with outside CEO succession. Using a panel dataset of 989 pollution-intensive Chinese firms from 2010 to 2022, we apply propensity score matching (PSM) to reduce endogeneity in CEO succession decisions, followed by fixed-effects regressions. The empirical results show that outside CEOs, particularly during their early tenure, are more likely to prioritize short-term financial performance over environmental goals—due to limited firm-specific knowledge and heightened external pressure. However, external board social capital (e.g., ties to government and industry associations) enhances resource access and post-appointment accountability, while internal social capital (e.g., co-working experience among directors) establishes common norms that facilitate strategic continuity. This study positions board social capital as a relational governance mechanism that complements formal oversight. The findings contribute to succession and environmental research by linking executive origin to sustainability outcomes and provide practical guidance on leveraging board networks to support leadership transitions.